Automating the search of molecular motor templates by evolutionary methods - Fernández-Rodríguez, Jose David; Vico-Vela, Francisco José (Elsevier, 2011)
Biological molecular motors are nanoscale devices capable of transforming chemical energy into mechanical work, which are being researched in many scientific disciplines. From a computational point of view, the characteristics and dynamics of these motors are studied at multiple time scales, ranging from very detailed and complex molecular dynamics simulations spanning a few microseconds, to extremely simple and coarse-grained theoretical models of their working cycles. However, this research is performed only in the (relatively few) instances known from molecular biology. In this work, results from elastic network analysis and behaviour-finding methods are applied to explore a subset of the configuration space of template molecular structures that are able to transform chemical energy into directed movement, for a fixed instance of working cycle. While using methods based on elastic networks limits the scope of our results, it enables the implementation of computationally lightweight methods, in a way that evolutionary search techniques can be applied to discover novel molecular motor templates. The results show that molecular motion can be attained from a variety of structural configurations, when a functional working cycle is provided. Additionally, these methods enable a new computational way to test hypotheses about molecular motors.
The first author is supported by a FPU grant (AP2007-03704) from the Ministerio de Educación of the Spanish Government, and has been supported by the BioEmergences project (code 28892) of the Sixth Framework Programme of the European Union. Our research group has been partially supported by the local government (Junta de Andalucía) through a grant for the GENEX project (P09-TIC-5123).
Keywords: Biología computacional; Molecular motor; Elastic network model; Behavior-ﬁnding